Are argentinian vegetable oils subsidized? - Fernández-Baca, Jorge (2001)
The Peruvian producer of vegetal cooking oil are trying to deter the entry of imports coming from Argentina, claiming that these products have a 10% subvention from the Argentinian Government and that this subsidy allows them to compete unfairly with the Peruvian producers. They are asking INDECOPI to apply a countervailing duty in order to outweigh the negative effects of this alleged subvention. This paper analyzes the validity of the arguments held by the plaintiffs and the convenience of fulfilling their requests.